Contestation and resistance: the politics of and around transitional justice in Nepal. Issue 1 (2nd January 2018) - Selim, Yvette
Abstract: The shift to adopting holistic approaches in transitional justice indicates an intention to pay (greater) attention to politics in transitional justice. However, transitional justice actors frequently encounter difficulties in doing so, misread politics and misconstrue where to locate it in post-conflict contexts. Using research from Nepal I argue that there is considerable political activity taking place that challenges transitional justice on multiple scales. This research demonstrates that actors frequently seek to advance their interests and make claims utilising the process, institutions and language of transitional justice. In particular, I draw upon resistance literature and contentious politics literature to elucidate the complex relationships and interactions at the local and national level, which are often omitted from discussions about transitional justice in Nepal. Accordingly, I argue it is more useful to consider actors' actions in relation to transitional justice on a continuum where there is co-option, resistance, contestation and compliance with a wide range of variation within each.